Formação em saúde coletiva: desafios e experiências em uma universidade no Oeste do Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
Introduction: This study was conducted in Santarém, in western Pará, where the Federal University of Western Pará (Ufopa) is located and its presence in Santarém, is established amid difficulties of access to health services in the region. Ufopa has been building a space to face obstacles in relation to health, taking into consideration important milestones within Public Health, involving the different knowledge and practices of the population, such as the completeness and equity of the Unified Health System (SUS), trying to overcome the biologicist idea and the hegemonic clinical model, emphasizing the social valorization, the bond between population and health professionals and the establishment of a basic attention focused on the logic of care and not the disease. The creation of the Bachelor of Public Health (BSC) course was structured based on the pedagogy of autonomy, emphasizing the formation of critical and reflective students in order to respond to the current demands of SUS. Objective: To analyze the training in Collective Health at a University in Western Pará. Materials and Methods: This is a qualitative, descriptive research of the type experience report on the training of professionals in Collective Health, regarding the challenges found in University in Western Pará. To organize the records, the study objectives and formulation of categories were used as a guiding basis: academic experiences of teaching, extension and research, challenges of collective health education and contributions from the Sanitarist, based on experiences and observations of the author in the internships and other activities. Results: BSC is an example of training that intertwines the technique to work in management spaces, attention, and has a deeper look at health care, at a time when most professionals act in a fragmented manner. Although this course does not have the necessary recognition in some bodies, some health sectors already know it and know how to direct the intern to the activities in the BSC competence service, contributing to its formation. Final Considerations: There is a need to broaden information about the Collective Health professional, so that it is known what their roles in the SUS and the need for them in the system so that they can act as a strategic actor, being this professional of paramount importance in promoting, prevention, health recovery, as well as reducing the workload of other professionals.
Keywords: Saúde Pública; Sistema Único de Saúde; Educação superior; CNPQ:: CIÊNCIAS DA SAÚDE